﻿Early stage of invasion of the quagga mussel (Dreissena rostriformis bugensis) within the interconnected lakes Lough Ree and Lough Derg of the Shannon River system, Ireland - Oscar Flynn; Dan Minchin; Martina B. Caplice; Kate O’Leary; Heather Swanwick; Jan-Robert Baars (Aquatic Invasions)
Quagga and zebra mussels of the genus Dreissena are two of the most impactful freshwater invasive alien species that have spread widely across the globe. These species attach to natural and artificial substrates, form dense populations and filter large volumes of water causing ecological and economic damage. Following the quagga mussel’s discovery in the Shannon River system in Ireland, this study assesses its local distribution, population density, relative abundance, and population structure in the interconnected lakes Lough Ree and Lough Derg in order to determine the likely year and location of its introduction. Polymodal length-frequency analysis was used to distinguish between year cohorts and estimate growth rates. The quagga mussel is established widely across both lakes and is settling on a range of artificial surfaces, natural substrates, dead shells, plant material, and other invasive bivalves. High densities of quagga mussels exceeding 20 000 individuals per m2 were present on artificial surfaces in Lough Ree with total dreissenid densities reaching 26 758 per m2. The relative abundance of quagga mussels to zebra mussels on natural substrates is high in Lough Ree (up to 94.7%) and low in Lough Derg (up to 16.8%). Two to four year cohorts were present at all sites, with quagga mussels attaining large shell sizes over 34 mm in length. Growth varied between sites with a maximum estimated yearly growth rate of 16.8 mm. The time and place of the quagga mussel’s initial introduction in Ireland is still uncertain, but its widespread distribution, population structure, and high population density and relative abundance suggest it was first introduced to Lough Ree in 2016 or 2017.